A novel DOPO-based flame retardant containing benzimidazolone structure with high charring ability towards low flammability and smoke epoxy resins - Wang, Hao; Li, Shan; Zhu, Zongmin; Yin, Xianze; Wang, Luoxin; Weng, Yunxuan; Wang, Xuyi (Polymer degradation and stability, 2021)
•A phosphaphenanthrene/benzimidazolone-containing flame retardant (POBDBI) was synthesized successfully.•POBDBI imparted excellent flame retardancy and smoke suppression to EP.•POBDBI exerted flame-retardant effect both in condensed phase and gaseous phase. A novel flame retardant POBDBI was generated by the reaction of p-dibenzaldehyde, 5-amino-2-benzimidazolinone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and employed to epoxy resin. The structure of POBDBI was measured by FT-IR and NMR tests. Then flame-retardant EP was fabricated by using POBDBI as a flame-retardant. The thermal stability, flame-retardant performance and fire behavior were investigated by a serious of comprehensive instruments. Combustion tests show the flame-retardant performance of composite materials has been significantly improved. For example, the EP/POBDBI-1.0 with the phosphorus content of 1.0% accorded a V-0 rating and its limiting oxygen index (LOI) value increased to 36.5%. Besides, total smoke production (TSP), peak heat release rate (PHRR) and total heat release (THR) of EP/POBDBI-1.0 dropped significantly, and the corresponding values were decreased by 48.4%, 48.9% and 8.7%, respectively. At the same time, the composition, morphology of chars and gaseous products of POBDBI were studied by X-ray photoelectron spectroscopy (XPS), FT-IR, scanning electron microscope (SEM) and Py-GC/MS. These results presented that POBDBI could not only exerted free radical capture effect, but also enhanced the density of char residue.